Implementasi Sistem Keamanan Pesan Text Dengan Teknik Steganografi Menggunakan Metode Least Significant Bit (LSB) - Apriansyah Apriansyah; Harun Mukhtar; Mitra Unik (Universitas Muhammadiyah Riau, 2020)
Indonesia, most cyber incidents reported by respondents relate to loss or leakage of business information such as internal records, information related to customers, employees and intellectuals. This worries the misuse of information held by irresponsible parties. in order to protect information so that it is not misused by unauthorized parties, then an attempt is made to hide the actual information on other information called steganography by using the Least Significant bit (LSB) method and to see the image quality value containing the message using the MSE calculation (Mean Square Error) and PSNR (Peak signal to noise ratio). The process of inserting messages is successfully carried out and produces extraction steganographic images. From testing the picture it can be concluded that the results of the steganography application must be invisible or not visible in plain view, as the purpose of this study is to increase the security sent to arrive at the recipient.